Determination of Hydration Window for Cryopreservation of Three Citrus Species - Ugap, Amyita Witty (2008)
The objective of this study was to determine the optimal hydration window for successful cryopreservation of Citrus madurensis, C. grandis and C. reticulata seeds in relation to their tolerance to desiccation and freezing. Initially, seed tolerance to desiccation and freezing were empirically investigated based on the seed survival, before and after freezing in liquid nitrogen (LN). Seeds were desiccated in a laminar air flow (LAF) (55% RH) and over silica gel (SO) (5% RH) for different periods (0, 12, 24, 36, 48, 60, 72, 96 and 120 hours). The dehydration rates were similar for both methods employed for the first 48 hours of desiccation but differed thereafter, with seeds desiccated using SO reaching water content below 0.10 gH20.g-1 fresh weight (fw) earlier than using LAF. Significant decline in seed survival was observed with decrease in water content of the three citrus species. Water content for desiccation sensitivity (We DS) measured as the water content when significant decline in survival was observed. We DS for seeds desiccated in LAF was 0.14, 0.18 and 0.07 gH20.g-1 fw for C. madurensis, C. grandis and C. reticulata, respectively. As for SO, it was 0.17, 0.23 and 0.08 gH20.g-, fw for C. madurensis, C. grandis and C. reticulata. In relation to freezing tolerance, the water content at the highest survival achieved or termed the high moisture freezing limit (HMFL) was 0.09, 0.l3 and 0. 1 1 gH20g" fw for C. madurensis, C. grandis and C. reticulata when seeds were desiccated in LAF. As for seeds desiccated over SO, the HMFL was 0. 10 gH20.g-' fw for C. madurensis and 0.08 gH20.g-' fw for C. grandis and C. reticulata. This resulted in WCDS having greater value than HMFL. Therefore WeDS was determined based on 50% reduction in seed survival and the values were 0.07 gH20.g-' fw for C. madurensis and 0.06 gH20.g-1 fw for C. grandis and C. reticulata when desiccated in LAF. As for SO, it was 0.06, 0.08 and 0.05 gH20.g-' fw for C. madurensis, C. grand is and C. reticulata. Seeds exposed to LN, subsequent to desiccation to -0.10 gH20.g-' fw water content using the LAF resulted in better survival (40-50%) as compared to SO «40%). However, the water content obtained would depend on the initial water content and the seed-toseed variation.